Screening and management options for severe thinness during pregnancy in India. Issue 3 (1st November 2021) - Sethi, Vani; Choedon, Tashi; Chowdhury, Ranadip; Bhatia, Neena; Dinachandra, Konsam; Murira, Zivai; Bhanot, Arti; Baswal, Dinesh; de Wagt, Arjan; Bhargava, Madhavi; Meshram, Indrapal Ishwarji; Babu, Giridhara R.; et al.
Abstract: This paper answers research questions on screening and management of severe thinness in pregnancy, approaches that may potentially work in India, and what more is needed for implementing these approaches at scale. A desk review of studies in the last decade in South Asian countries was carried out collating evidence on six sets of strategies like balanced energy supplementation (BEP) alone and in combination with other interventions like nutrition education. Policies and guidelines from South Asian countries were reviewed to understand the approaches being used. A 10‐point grid covering public health dimensions covered by World Health Organization and others was created for discussion with policymakers and implementers, and review of government documents sourced from Ministry of Health and Family Welfare. Eighteen studies were shortlisted covering Bangladesh, India, Nepal, and Pakistan. BEP for longer duration, preconception initiation of supplementation, and better pre‐supplementation body mass index (BMI) positively influenced birthweight. Multiple micronutrient supplementation was more effective in improving gestational weight gain among women with better pre‐supplementation BMI. Behavior change communication and nutrition education showed positive outcomes on dietary practices like higher dietary diversity. Among South Asian countries, Sri Lanka and Nepal are the only two countries to have management of maternal thinness in their country guidelines. India has at least nine variations of supplementary foods and three variations of full meals for pregnant women, which can be modified to meet additional nutritional needs of those severely thin. Under the National Nutrition Mission, almost all of the globally recommended maternal nutrition interventions are covered, but the challenge of reaching, identifying, and managing cases of maternal severe thinness persists. This paper provides four actions for addressing maternal severe thinness through available public health programs, infrastructure, and human resources. Synopsis: This paper suggests four actions for addressing maternal severe thinness in public health programs.